Defining the Most Appropriate Delivery Mode in Women with Inflammatory Bowel Disease: A Systematic Review. Issue 5 (14th April 2017) - Foulon, Arthur; Dupas, Jean-Louis; Sabbagh, Charles; Chevreau, Julien; Rebibo, Lionel; Brazier, Franck; Bouguen, Guillaume; Gondry, Jean; Fumery, Mathurin
Abstract : Introduction: High cesarean section (CS) rates are observed in patients with inflammatory bowel disease (IBD), but limited data are available to support this decision. We conducted a comprehensive review to evaluate the most appropriate mode of delivery in women with IBD according to disease phenotype and activity, as well as surgical history. Materials and Methods: We searched MEDLINE (source PubMed) and international conference abstracts, and included all studies that evaluated digestive outcome after delivery in patients with IBD. Results: A total of 41 articles or abstracts were screened, and 18 studies were considered in this review, with sample sizes ranging from 4 to 229 patients and follow-up ranging from 2 months to 7.7 years. Pooled CS rates in patients without Perianal Crohn's disease (PCD), healed PCD or active PCD, were 27%, 43%, and 46%, respectively. Regarding the median rate of new PCD (3.0% [IQR, 1.5–11.5] versus 6.5% [0–19.7]) or PCD recurrence (13.5% [3.2–32.7] versus 45% [0–58]), no increase was observed in patients with vaginal delivery compared to CS, but for patients with an active disease, worsening of symptoms was noted in two-thirds of cases. Episiotomy, perianal tears, and instrumental delivery did not influence the incidence of PCD. In patients with ileal pouch anal anastomosis, uncomplicated vaginal delivery seemed to moderately influence pouch function, with no significant difference in terms of overall continence, daytime, or night-time stool frequency, or incontinence. However, these parameters seemed negatively impacted by a complicated vaginal delivery. Conclusions: New long-term data from well-designed studies are needed, but our review suggests that systematic CS in patients suffering from IBD should probably be limited to women at risk of perineal tears and obstetric injuries, with an active PCD, or with ileal pouch anal anastomosis.